Tindak Tutur Ilokusi dalam Lirik Lagu Tanpa Cinta Karya Tiara Andini: Kajian Pragmatik - Anwar, Alifia Nabila Putri; Maulana, Adam; Lukman, Diva Sania; Mabruroh, Siti; Ramadhanti, Annisa (J-LELC: Journal of Language Education, Linguistics, and Culture, 2026)
The objective of this study is to describe the types of illocutionary acts contained in the lyrics of the song Tanpa Cinta by Tiara Andini. A qualitative descriptive method is used to describe in detail the various types of speech acts actualized through the lyrics of the song. Data were obtained from Tiara Andini's official YouTube account related to the lyrics of Tanpa Cinta using the listening and note-taking technique. Using a pragmatic perspective as a framework for analysis, specifically Searle's (1979) theory of illocutionary acts, and based on the data analyzed, the following types of speech acts were found: A pragmatic perspective was used as the analytical framework, specifically Searle's (1979) theory of illocutionary acts. Based on the data analyzed, the types of speech acts found in the lyrics of Tiara Andini's song Tanpa Cinta were assertive, directive, expressive, and commissive. In this case, assertive speech acts dominate over other speech acts, and no declarative speech acts were found. The dominance of assertive speech acts occurs because the lyrics of Tanpa Cinta largely represent the speaker's depiction of the situation, beliefs, and assessments of the relationship they are experiencing, so that the speaker is committed to the truth of what they are saying. This indicates the speaker's effort to convey information or state a condition with a commitment to the truth of the utterance.